Perbandingan Representasi Raja Alfred dalam “The Life of King Alfred” oleh Asser dan Prabu Hayam Wuruk dalam “Negarakertagama” oleh Mpu Prapanca - Nur, Hilmi Asyam; Thomas, Matthew Alexander; Naila, Rifa Wildanin (Jurnal Sosial Humaniora Sigli, 2023)
The research contrasts two historical texts which tell about two different influential kings of Old England and Indonesia, two great nations, namely The Life of King Alfred, written by Asser, and Nagarakretagama, written by Mpu Prapanca. Both texts are biased since the writers are admirers of the Kings. Therefore, the research is aimed to unveil the similarities and differences of the two texts in depicting the Kings. In Asser's 'Life', Asser attempted to lift King ALfred's name by showing the King's achievements throughout his reign. However, many researchers found oddities within the text and suspected that there are embedded political purposes. Similarly, Nagarakretagama is a form of praise towards Hayam Wuruk which tells about the glory of Majapahit and The King.  Mpu Prapanca used historical background to praise the King and the kingdom's magnificence. Both texts have basic similarities in lifting the names and covering the lackness of the Kings. However, since both texts have propaganda properties to some extent, both could not be considered as accurate sources of history.Keywords: Hayam Wuruk, Alfred The Great, Majapahit, Wessex, Asser, Mpu Prapanca,Comparative, History